COMPARATIVE ANALYSIS OF DIPLOMATIC TERMINOLOGY IN DOCUMENTARIES IN RUSSIAN AND UZBEK LANGUAGES - Alauddinova Rukhsora Ramazan Kizi (European International Journal of Multidisciplinary Research and Management Studies, 2024)
Studying the language of the diplomatic documentation work, we understand standardization as a form of terminology, the mechanisms, and procedures of which are aimed, first of all, at the formation of an adequate and consistent system of the diplomatic terms (diplomatic terminology) that meet the goals and objectives of modern diplomatic relations. In contemporary globalization processes and the increasing role of inter-country communication, the study of the vocabulary reflecting the diplomatic business sphere contributes to the establishment of a constructive and mutually beneficial inter-country dialogue and good international contacts.